A New Record of the Genus Orchisia (Diptera: Muscidae) from Korea - Suh, Sang Jae; Yong Jung Kwon (Animal systematics, evolution and diversity, 2017)
The fly genus Orchisia Rondani belonging to the tribe Coenosiini of the family Muscidae, known to be distributed throughout old world, is newly recorded in Korean fauna, along with the type species O. costata (Meigen, 1826). This genus has been known to include only two species, O. costata and O. subcostata Cui, Xue et Liu, 1995. These flies can be readily distinguished by the other related taxa of the tribe Coenosiini in having prominent color pattern on wings. The Korean population has been observed on the grass vegetation at marsh area. Photographs of external features and male genitalic characters are provide.